Spatial-temporal Changes and Driving Forces of Nanning San Jie Liang Xiang from 1947 to 2020 - Wei Hanyu; Chen Jiaxin; Wang Guoguang (Lodz University of Technology Press, 2023)
The urban space remains and traditional cultures face the contradiction between development and conservation. In urban morphology study, GIS and Spatial Syntax enables quantitative analysis of morphology evolution and explorations of the driving forces through which could control the change of the urban form. This paper is about one case study of San Jie Liang Xiang, Nanning, China. Firstly, four critical periods are defined. And the morphological characteristics and structural relationships of street blocks in each period are extracted. Secondly, space syntax is used to study the morphological evolution in terms of its spatial configuration and the relationship between spatial characteristics and urban development. Third, the morphological evolution and evolution dynamics are matched to explain the law of spatial-temporal change. Finally, this paper attempts to establish spatial form element control to guide the practice, combining form type with form design. In conclusion, the driving forces affect the morphology in the development period. Following the law of morphological evolution, morphological guidance and control based on driving forces research may provide solutions for renewing sustainable historical street blocks.
Keywords: historical street blocks; morphology evolution; driving forces; typo-morphology; space syntax; historyczne bloki uliczne; ewolucja morfologii; siły napędowe; typo-morfologia; składnia przestrzeni